1987
DOI: 10.1177/00220345870660081401
|View full text |Cite
|
Sign up to set email alerts
|

Possible Physico-Chemical Processes in Human Dentin Caries

Abstract: This study correlated ultrastructural observations on the presence of beta-tricalcium phosphate (beta-TCP) in arrested dentin caries with physico-chemical observations on the in vitro formation of Mg-substituted beta-TCP. The ultrastructural studies were made using high-resolution transmission electron microscopy (TEM) with the capability of microdiffraction and microanalysis on sites less than 10 nm in diameter. Mg-substituted beta-TCP was obtained, by a precipitation method, from solutions with Mg/Ca molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
22

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 13 publications
5
58
0
22
Order By: Relevance
“…Lower magnesium (Mg) amount present in sclerotic dentin is in agreement with literature data [40]. Mg is a natural constituent of hydroxyapatite present in peritubular and intertubular dentin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lower magnesium (Mg) amount present in sclerotic dentin is in agreement with literature data [40]. Mg is a natural constituent of hydroxyapatite present in peritubular and intertubular dentin.…”
Section: Discussionsupporting
confidence: 90%
“…Mg is a natural constituent of hydroxyapatite present in peritubular and intertubular dentin. Magnesium is the first element to be lost during dentin demineralization process, even prior to Ca and P [40]. Remineralization presents restored mineral content (non-apatite) often with no Mg on its composition.…”
Section: Discussionmentioning
confidence: 99%
“…Rhombohedral crystals were often observed (1) in den tinal tubules that underlie both active and arrested lesions Daculsi et al, 1979;Frank and Voegel, 1980;Daculsi et al, 1987], (2) in dentinal tubules under neath surface areas that show evidence of occlusal attri tion [Mendis and Darling, 1979] and (3) in dentinal tubules of specimens obtained from naturally desensitized areas of hypersensitive teeth [Yoshiyama et al, 1989[Yoshiyama et al, ,1990. They were identified as whitlockite crystals (Mg-substituted (i-tricalcium phosphate, P-TCMP) Vahl et al, 1964;Takuma et al, 1969;Daculsi et al, 1979Daculsi et al, , 1987Frank and Voegel, 1980], Daculsi et al [1987] suggested that the formation of crystals of [1-TCMP in arrested den tin caries occurs stepwise by the dissolution of intertubular dentin, the saturation of the solution in the dentinal tu bules with calcium, phosphate and magnesium ions, and final rcprccipitation of [1-TCMP crystals in the tubules as suggested by Daculsi et al [1987], The coexistence of large crystals of Mg-substituted |)-TCMP and small needle-like crystals, most probably representing apatite ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…They were identified as whitlockite crystals (Mg-substituted (i-tricalcium phosphate, P-TCMP) Vahl et al, 1964;Takuma et al, 1969;Daculsi et al, 1979Daculsi et al, , 1987Frank and Voegel, 1980], Daculsi et al [1987] suggested that the formation of crystals of [1-TCMP in arrested den tin caries occurs stepwise by the dissolution of intertubular dentin, the saturation of the solution in the dentinal tu bules with calcium, phosphate and magnesium ions, and final rcprccipitation of [1-TCMP crystals in the tubules as suggested by Daculsi et al [1987], The coexistence of large crystals of Mg-substituted |)-TCMP and small needle-like crystals, most probably representing apatite ( fig. 14), may be the result of a depiction of Mg2+ ions from the fluid phase during the formation of (f-TCMP and the subse quent formation of Mg-poor apatite.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-grained deposits observed in natural lesions have been identified as apatitic, while coarse gran ules similar to those seen in several specimens in the pre sent study have been identified as WH [e.g.. Frank and Voegel. 1980;Daculsi et al, 1987;Schtipbach et ah. 1992].…”
Section: Shellismentioning
confidence: 99%